Allometric Scaling in Pharmacokinetic Studies in Anesthesiology. (2nd February 2022) - Eleveld, Douglas J.; Koomen, Jeroen V.; Absalom, Anthony R.; Su, Hong; Hannivoort, Laura N.; Struys, Michel M. R. F.
Abstract : A clinical review is presented of basic allometric scaling theory and its application to pharmacokinetic models in anesthesia and other fields in the biologic sciences.